2011
DOI: 10.1017/s0047279411000341
|View full text |Cite
|
Sign up to set email alerts
|

Combating In-Work Poverty in Continental Europe: An Investigation Using the Belgian Case

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…Interest in EITC type schemes remains strong however, in the public debate and in the academic literature (Kenworthy, 2011;Figari, 2011, Allègre andJaerhling, 2011;Crettaz, 2011;Marx et al, 2012;Aaberge and Flood, 2013). That interest seems entirely legitimate.…”
Section: Kingdom and The Earned Income Credit (Eitc) In The United Stmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in EITC type schemes remains strong however, in the public debate and in the academic literature (Kenworthy, 2011;Figari, 2011, Allègre andJaerhling, 2011;Crettaz, 2011;Marx et al, 2012;Aaberge and Flood, 2013). That interest seems entirely legitimate.…”
Section: Kingdom and The Earned Income Credit (Eitc) In The United Stmentioning
confidence: 99%
“…This cost can only be avoided by making the amount of the tax credit itself smaller, but in that case the anti-poverty effect is reduced. Simulations by Bargain and Orsini (2007) for Germany, France and Finland, by Figari (2011) for four southern European countries (Italy, Spain, Portugal and Greece) and by Marx et al (2012) for Belgium shed doubt over the applicability of EITC type systems in other settings. In an earlier study, Bargain and Orsini (2007) investigated the effects on poverty of the hypothetical introduction of the British scheme (as it was in place in 1998) in Germany, France and Finland, using EUROMOD for 2001.…”
Section: Kingdom and The Earned Income Credit (Eitc) In The United Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a number of researchers have suggested that temporary employment can damage health, whether the health outcome being measured is psychological distress, depression, physical health, morbidity or chronic disease, including when the health status is selfrated [21,22]. Furthermore, some researchers have indicated that the negative health effects of temporary employment may be outcome-specific and that the poorer health of temporary workers may depend on their social and environmental context [23][24][25][26][27]. Notwithstanding, there is agreement among researchers that women continue to do worse than men in health terms within precarious employment [24,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Income poverty is the most popular indicator used (i.e. Backman and Ferrarini 2010;Casalone and Sonedda 2013;Figari, Matsaganis and Sutherland 2013;Marx, Vanhille and Verbist 2012;Salanauskaite and Verbist 2013;Stewart and Huerta 2009;Yakut-Cakar, Erus and Adaman 2012). Some studies use material deprivation: Nelson (2012) studies the effect of social assistance on material deprivation; Saunders and Wong (2011) use material deprivation to assess the adequacy of Australian benefits to single pensioners.…”
Section: Introductionmentioning
confidence: 99%